98P Results from a phase I study of MK-1308 (anti–CTLA-4) plus pembrolizumab in previously treated advanced small cell lung cancer. (15th December 2019) - Cho, B C; Yoh, K; Bar, J; Nagrial, A; Spigel, D R; Gutierrez, M; Kim, D-W; Kotasek, D; Rasco, D; Niu, J; Satouchi, M; Ahn, M-J; et al.
Abstract: Background: An ongoing open-label, multiarm, multicenter, phase I study of the anti–CTLA-4 antibody MK-1308 in combination with pembrolizumab in advanced solid tumors (NCT03179436) revealed manageable safety and promising efficacy in patients (pts) with advanced non-small cell lung cancer receiving first-line therapy [Perets et al. J Clin Oncol. 2019;37(suppl):2558]. Here we report data from the small cell lung cancer (SCLC) cohort of this study. Methods: In the dose confirmation phase, pts with advanced SCLC received MK-1308 at 75 mg Q6W + pembrolizumab 200 mg Q3W (up to 35 cycles). The primary end point was safety, and the secondary end point was ORR based on blinded independent central review (BICR) per RECIST v1.1. PFS based on BICR per RECIST v1.1 and OS were exploratory end points. The database cutoff date for this analysis was June 3, 2019. Results: Forty pts with previously treated advanced SCLC (second-line or beyond) were enrolled and dosed; median duration of follow-up was 11 mo. At data cutoff, 32 pts (80%) discontinued study treatment—23 (58%) due to progressive disease, 4 (10%) due to AE, 2 (5.0%) due to clinical progression—and 3 (7.5%) withdrew consent. Median age was 66 years; 60% of pts were male and 65% had ECOG PS 1 at baseline. Seven pts achieved partial response according to BICR assessment, for an ORR of 18% (95% CI, 7.3-33). Eight pts (20%) had a best overall response of stable disease and 21 (53%) had progressive disease. Response duration ranged from 2.9 to 8.4+ mo. At the time of the data cutoff, 5 of 7 responses (71%) were ongoing. Median time to response was 2.1 mo (range, 1.1-12). Median PFS was 2.0 mo (95% CI, 1.9-3.9), and the 6-mo PFS rate was 26%. Median OS was 11 mo (95% CI, 5.9-not reached), and the 6-mo OS rate was 66%. Treatment-related adverse events (TRAEs) as determined by the investigator occurred in 32 pts (80%). Grade 3 TRAEs were reported in 11 pts (28%); no grade 4-5 events were reported. Three pts (7.5%) discontinued treatment due to TRAEs. Conclusion: In heavily pretreated pts with SCLC, MK-1308 + pembrolizumab was generally well tolerated with encouraging antitumor activity. Clinical trial identification: NCT03179436. Editorial acknowledgement: Medical writing and/or editorial assistance was provided by Holly C. Cappelli, PhD, CMPP, and Dana Francis, PhD, of the ApotheCom pembrolizumab team (Yardley, PA, USA) and funded by Merck Sharp & Dohme Corp, a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Legal entity responsible for the study: Merck Sharp and Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Funding: Merck Sharp and Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Disclosure: B.C. Cho: Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self): Novartis; Honoraria (self), Research grant / Funding (self): Bayer; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self): AstraZeneca; Honoraria (self), Research grant / Funding (self): MOGAM Institute; Honoraria (self), Research grant / Funding (self): Dong-A ST; Honoraria (self), Research grant / Funding (self), Licensing / Royalties: Champions Oncology; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self): Janssen; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self): Yuhan; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self): Ono; Honoraria (self), Research grant / Funding (self): Dizal Pharma; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self): MSD; Advisory / Consultancy: Boehringer-Ingelheim; Advisory / Consultancy: Roche; Advisory / Consultancy: Bristol-Myers Squibb; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Eli Lilly; Advisory / Consultancy: Takeda; Shareholder / Stockholder / Stock options: TheraCanVac Inc; Shareholder / Stockholder / Stock options: Bridgebio Therapeutics; Shareholder / Stockholder / Stock options: Gencurix Inc. K. Yoh: Research grant / Funding (institution): MSD. J. Bar: Advisory / Consultancy, Research grant / Funding (self), Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy: MSD; Advisory / Consultancy, Research grant / Funding (institution): Boehringer Ingelheim; Advisory / Consultancy, Research grant / Funding (institution): Roche; Advisory / Consultancy, Research grant / Funding (institution): Bristol-Myers Squibb; Advisory / Consultancy: Takeda; Advisory / Consultancy, Research grant / Funding (institution): Abbvie; Advisory / Consultancy: OncoHost; Advisory / Consultancy: VBL; Research grant / Funding (institution): Pfizer. A. Nagrial: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): MSD; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): AZ; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Roche; Research grant / Funding (institution): Beigene; Research grant / Funding (institution): Incyte. D.R. Spigel: Leadership role: Centennial Medical Center; Travel / Accommodation / Expenses: AstraZeneca; Travel / Accommodation / Expenses: Boehringer-Ingelheim; Travel / Accommodation / Expenses: Celgene; Travel / Accommodation / Expenses: Eli Lilly; Travel / Accommodation / Expenses: EMD Serono; Travel / Accommodation / Expenses: Bristol-Myers Squibb; Travel / Accommodation / Expenses: Genentech; Travel / Accommodation / Expenses: Genzyme; Travel / Accommodation / Expenses: Intuitive Surgical; Travel / Accommodation / Expenses: Merck; Travel / Accommodation / Expenses: Pfizer; Travel / Accommodation / Expenses: Purdue Pharma; Travel / Accommodation / Expenses: Spectrum Pharmaceuticals; Travel / Accommodation / Expenses: Sysmex. M. Gutierrez: Shareholder / Stockholder / Stock options: COTA; Advisory / Consultancy, Speaker Bureau / Expert testimony: Eli Lilly; Advisory / Consultancy: Esanex; Advisory / Consultancy: Guardant 360; Speaker Bureau / Expert testimony: Merck; Speaker Bureau / Expert testimony: Bristol-Myers Squibb; Speaker Bureau / Expert testimony: Foundation Medicine. D-W. Kim: Research grant / Funding (institution): Alpha Biopharma; Research grant / Funding (institution): AstraZeneca/Medimmune; Research grant / Funding (institution): Hanmi; Research grant / Funding (institution): Janssen; Research grant / Funding (institution): Merus; Research grant / Funding (institution): Mirati Therapeutics; Research grant / Funding (institution): MSD; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): ONO Pharmaceutical; Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): Roche/Genentech; Research grant / Funding (institution): Takeda; Research grant / Funding (institution): TP Therapeutics; Research grant / Funding (institution): Xcovery; Research grant / Funding (institution): Yuhan. D. Rasco: Research grant / Funding (institution): Merck; Research grant / Funding (institution): Regeneron. M. Satouchi: Honoraria (self), Research grant / Funding (institution): MSD. M-J. Ahn: Honoraria (self), Advisory / Consultancy: Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy: ONO; Honoraria (self), Advisory / Consultancy: MSD; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Takeda; Advisory / Consultancy: Lilly; Advisory / Consultancy: Alpha Pharm. D.H. Lee: Honoraria (self): AbbVie; Honoraria (self): AstraZeneca; Honoraria (self): Boehringer-Ingelheim; Honoraria (self): Bristol-Myers Squibb; Honoraria (self): ChongKunDang; Honoraria (self): CJ Healthcare; Honoraria (self): Eli Lilly; Honoraria (self): Janssen; Honoraria (self): Menarini; Honoraria (self): Merck; Honoraria (self): MSD; Honoraria (self): Mundipharma; Honoraria (self): Novartis; Honoraria (self): Ono; Honoraria (self): Pfizer; Honoraria (self): Roche; Honoraria (self): Samyang Biopharm; Honoraria (self), Advisory / Consultancy: ST Cube; Honoraria (self): Takeda. C. Maurice-Dror: Travel / Accommodation / Expenses: Janssen; Travel / Accommodation / Expenses: Pfizer; Travel / Accommodation / Expenses: Roche. S. Siddiqi: Full / Part-time employment: Merck & Co., Inc.. X. Li: Full / Part-time employment: Merck & Co., Inc.. J. Cyrus: Leadership role, Travel / Accommodation / Expenses, Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck & Co., Inc.. R.A. Altura: Travel / Accommodation / Expenses, Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck & Co., Inc.. R. Perets: Advisory / Consultancy: Karyopharm; Advisory / Consultancy: BiolineRx. All other authors have declared no conflicts of interest.